412 - An Affect Education Model for Caregivers: Managing Behavioural and Psychological Symptoms of Dementia. (October 2020) - Schwartz, Ken; Madan, Robert; Sham, Rosalind; Gardner, Sandra
Abstract : Introduction: Providing care for people with behavioural and psychological symptoms of dementia is stressful as these individuals are commonly labelled as aggressive or resistant to care. Few studies have evaluated the impact of providing support to professional caregivers working in long-term care. Our mixed methods pilot study evaluated the impact of the innovative Affect Education Model among health care providers from two Toronto nursing homes. Methods: The two-person centred Affect Educational Model through the use of seven questions that encourage self-reflection teaches that problematic behaviours are co-constructed between individuals with BPSD and caregivers. Study procedures included recruiting nursing staff and personal support workers and teaching them the model in five weekly 30-minute group sessions. Qualitative measures in the form of focus groups were obtained. Quantitative measures were obtained through the use of five questionnaires. Results: Qualitative findings from focus groups identified four themes: facilitators and barriers perceived in current care delivery, the impact of the model experience on staff care delivery, reflections on being taught the model, and future model implementation. Quantitative results were also collected and discussed. Conclusions: The use of both pharmacologic and nonpharmacologic treatment of individuals with BPSD may be greatly enhanced by an interpersonal two-person Affect Education Model that emphasizes the importance of calming down and self-reflection. Future directions include expanding the model to family caregivers through the use of multimedia resources.